SOCIAL-PSYCHOLOGICAL ASPECTS OF YOUTH SUSCEPTIBILITY TO THE INTERNET IMPACT - I. V. Vorobyeva; O. V. Kruzhkova (Russian State Vocational Pedagogical University, 2017)
Introduction. Today, the process of socialization of modern youth takes place in absoutely other circumstances in comparison with former generations. The social activity of young people and teenagers is being developed not only in real but also in virtual space. The Internet environment, where new generation representatives actively manifest themselves, has significant effect on their life goals and behaviour. This influence can be positive and useful, on the one hand, and negative, on the other, deforming human mind and own personality. The aim of the present article is to identify, describe and analyze social and psychological factors of youth susceptibility to psychological and informational impact of the Internet environment.Methodology and research methods. A method of sociological questioning was applied to find out the characteristics of young people behaviour in virtual space, degree of their involvement in "a world web", and intensity of the Web-based interaction. Psychodiagnostic methods by A. V. Smirnov "Semantic universals of the information and cultural environment" were used for studying the peculiarities of young people attitude to the Internet.Results and scientific novelty. The features of attitudes of young people towards the use of the Internet, degree of their virtual environment immersion, frequency of usage and behaviour models on the Internet are considered. A risk group among examinees (data sample - n = 277, 14-25 years) is marked out and characterized. The representatives of this group showed high activity on the Internet, however, they do not draw attention to the Internet content: their relation to virtual space is based on aprioristic recognition of its need and usefulness with the accompanying denial of any propaganda of dangerous ideas and behaviour models which can endanger psychological health, own wellbeing and wellbeing of other people.Practical significance. The data obtained can be used for effective prevention of negative impact of information and social content of the Internet on young people singled out as a risk group.